2023
DOI: 10.1002/acn3.51765
|View full text |Cite
|
Sign up to set email alerts
|

Natural history and survival rate of familial amyloidosis with polyneuropathy: A nationwide databank

Abstract: Objective: Hereditary amyloid transthyretin (ATTRv) amyloidosis with polyneuropathy, a rare autosomal-dominant disease, has gained attention in recent years owing to treatment improvements. However, epidemiological real-world mega database of nationwide natural history and survival rates, especially with the specific mutation of Ala97Ser, are limited. Methods: Taiwan National Health Insurance Research Database contains data from over 23 million individuals; Among them, 175 ATTRv amyloidosis patients validated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
(92 reference statements)
0
2
0
Order By: Relevance
“…To what extent an environmental component contributes to FAP seems unresolved (Gonzalez- Duarte et al, 2012). Even though significant progress has been made in understanding -and treating -FAP at the molecular level, the mechanism of pathogenesis and the overall origin of the disease remain unclear (Benson and Kincaid, 2007;Tseng et al, 2023).…”
Section: Manuscript: Brief Communicationmentioning
confidence: 99%
“…To what extent an environmental component contributes to FAP seems unresolved (Gonzalez- Duarte et al, 2012). Even though significant progress has been made in understanding -and treating -FAP at the molecular level, the mechanism of pathogenesis and the overall origin of the disease remain unclear (Benson and Kincaid, 2007;Tseng et al, 2023).…”
Section: Manuscript: Brief Communicationmentioning
confidence: 99%
“…One study has reported that genetic variants located in the non-coding regions of the TTR gene affect the clinical outcome of the disease [11]. Even though significant progress has been made in understanding-and treating-hATTR at the molecular level, the mechanism of pathogenesis and the overall origin of the disease remain unclear [12,13]. It has previously been argued that some neurodegenerative diseases could be related to metal exposure [14][15][16][17], possibly of geochemical origin [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…One study has reported that genetic variants located in the non-coding regions of the TTR gene affect the clinical outcome of the disease [ 11 ]. Even though significant progress has been made in understanding—and treating—hATTR at the molecular level, the mechanism of pathogenesis and the overall origin of the disease remain unclear [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%